Implementasi Konseling Lintas Budaya dan Agama di Sekolah (Madaniyah, 2017)
This study aims to determine the form of counseling services across cultures and religions at MTsN Yogyakarta 2, and the effectiveness of these services in helping students solve problems of self-reliance in the emotional aspect. This type of research, including qualitative field research, with research subjects students of class IX, who have different backgrounds cultural and religions. Methods of data collection using observation and interview methods. Data were analyzed using critical analytical methods, including reviewing the primary idea about a scope of the problem that is enriched by the notion of relevant secondary. The results showed that at MTsN Yogyakarta 2 has carried out counseling services across cultures and religions well, and proved to be effective in addressing the problems of learners about the problem of independence in the emotional aspect. It can be shown from the significant change of the learner about his interactions with peers, and its ability to determine future options in the career field.